A cross-national comparison of Millennial consumers' initial trust towards an e-travel website. Issue 3 (12th March 2018) - Jensen, Jan Møller; Wagner, Corinna
Abstract : Purpose: The purpose of this paper is to examine Millennials' formation of trust towards a travel website and identify the similarities and the differences in trust formation among consumers from two countries – Denmark and Portugal. Design/methodology/approach: The study is based on online surveys conducted with convenience samples from two culturally-distant countries. Independent t -tests, structural equation modelling and multi-group analysis are used to verify the conceptual model and test the hypotheses. Findings: Results support a strong relationship between initial trust towards a travel website and consumers' behavioural intentions. The results also suggest that cultural differences between countries moderate the formation of initial trust and behavioural reactions hereto. Originality/value: The study provides new insights into understanding how Millennials from Portugal and Denmark form initial trust towards an e-travel website.